Dual Leadership and Local Policy Implementation: A Case Study of E-Government Implementation in Vietnam - Hung Dao (Policy & Governance Review, 2026)
This study investigates how dual local leadership—embodied by the Provincial Party Secretary and the Chairman of the Provincial People’s Committee—shapes divergent policy implementation strategies within Vietnam’s party-state governance model. Fo- cusing on the politically sensitive and institutionally novel domain of e-government, this study explores how local cadres adapt implementation strategies over time in response to varying levels of policy clarity and political consensus. Employing a qual- itative comparative case study of three provinces—Hue, Dak Lak, and Ben Tre—char- acterized by different e-government development trajectories and strategic choices, the analysis reveals that interactions between the Party and administrative apparatuses generate distinct degrees of political consensus, which, in turn, influence implementa- tion outcomes. The study identifies four emergent implementation types—Symbolic, Self-Directed, Disjointed, and Sustainable—and introduces the ambiguity–Consen- sus Matrix, a conceptual framework for understanding implementation dynamics in one-party regimes. By illuminating subnational political dynamics and the contingent role of dual leadership, this study contributes to the broader public policy literature on policy implementation in centralized authoritarian systems.